Feasibility of nationwide warehouse receipt system: An assessment of the potential for a nationwide warehouse receipt system and recommendation for the requisite legal and regulatory framework - Narayanan, Sudha; Hussain, Siraj; Rashid, Shahidur (International Food Policy Research Institute, 2024)
Warehouse receipts systems (WRS) have been used to tackle multiple challenges faced by farmers. In the absence of adequate collateral and consequent credit constraints, a WRS enables the use of inventory as collateral for loans, thus removing a key constraint farmers face. With growing digital reach, electronic based Negotiable Warehouse Receipts (e-NWR) that can be swapped, exchanged and traded and can assist in deepening financial markets while maintaining the integrity of the system. While e-NWRS can potentially address farmer level constraints, they can also be viewed from a larger policy perspective as a system that aids government plans for food security and manage public procurement operations better and more nimbly; it can also play a key role for enhancing the efficiency and food quality and safety along value chains by enabling mid-stream players like traders and importers to manage these chains better. This report seeks to inform the policy process around e-NWRS by focusing on the potential of Ware house Receipt Financing, more broadly, in the agricultural development of Bangladesh. To do this we review global evidence as well as evidence closer to home, within South Asia, to understand the pre-conditions and prerequisites for a successful system.